Evaluation of immiscible two-phase quasi-static displacement flow in rough fractures using LBM simulation: Effects of roughness and wettability - Xin Zhou; Jianlong Sheng; Ye, Zuyang (Capillarity, 2024)
Roughness and wettability of the fracture surface have crucial effects on the two-phase flow properties in many applications involving fractured rock. The immiscible quasi-static displacement flow is widely concerned in porous media, but this phenomenon has been rarely explored in rough-walled fractures. In this study, based on fractal theory and a matched fracture model, three-dimensional fractures with different roughness surfaces and uniform aperture distribution are generated. The lattice Boltzmann-based multicomponent Shan-Chen model is employed to simulate the quasi-static drainage process under various wettability conditions through rough fractures. In fractures with greater roughness and stronger wettability, the displacement process is usually more unstable with more tortuous invasion fronts, which leads to larger entry pressure and displacement resistance. Accordingly, more residual saturation of the wetting phase and lower displacement efficiency occurs under the same capillary pressure. During the invasion process, because of the transverse and delaying development of displacement fronts, the frontmost position is sometimes almost unchanged, while the wetting phase saturation sharply decreases showing a “step-like” type curve. The residual capture patterns are generally divided into two types: “isolated trapping” capture located in areas with drastic undulations of surface, and “water film” capture adsorbed to the fracture surface. Stronger wettability induces more second captures due to the greater adsorption of wetting phase to the fracture wall. A continuous increase in capillary pressure has no apparent effect on the variation in wetting phase saturation when it is greater than the entry pressure, and the first corner on the left side of capillary pressure-wetting phase saturation curves is relatively sharp. Document Type: Original article Cited as: Zhou, X., Sheng, J., Ye, Z. Evaluation of immiscible two-phase quasi-static displacement flow in rough fractures using LBM simulation: Effects of roughness and wettability. Capillarity, 2024, 11(2): 41-52. https://doi.org/10.46690/capi.2024.05.02